Xerxes and Babylonia - Waerzeggers, Caroline; Seire, Maarja (2018)
In the summer of 484 BCE Babylonia revolted against Xerxes, king of Persia. In recent years, a debate has crystallized around the nature of Xerxes’ response to this challenge. This volume continues and expands this debate. It collects nine essays on the cuneiform text corpus dated to the period before, during and after the revolts. This material enables the authors to evaluate the nature of Xerxes’ policies in the sphere of society, science, religion, law, administration and economy against the long-term history of the region. The contributions are by Paul-Alain Beaulieu, Johannes Hackl, Michael Jursa, Karlheinz Kessler, Mathieu Ossendrijver, Reinhard Pirngruber, Malgorzata Sandowicz and Caroline Waerzeggers.